Combustion Performance of Torrefied Coffee Parchment Briquettes: Effects of Particle Size and Briquetting Pressure - Juwaini; adi setiawan; Muhammad (Talenta Publisher, 2025)
A substantial amount of coffee plantation waste is generated in Aceh highland, yetits utilization remains limited. Most of the wastes are dumped on the ground, whilecoffee parchment is often burned without further application. This study exploresthe conversion of coffee parchment into briquettes, focusing on their combustioncharacteristics. The parchment were subjected to torrefaction process attemperatures ranging from 240°C to 270°C and then ground to particle sizes of 40,60, and 80 mesh. Briquettes were formed using 10% tapioca flour as a binder andcompressed simultaneously for 20 pieces of briquettes at pressures of 300, 400,and 500 kg/cm². The resulting briquettes, with dimensions of 37×28×28 mm,exhibited a density of 0.63 g/cm³ and a combustion rate of 0.37 g/min, enabling aburn duration of up to 105 minutes and a peak temperature of 435°C. The bestperformance was achieved using a particle size of 60 mesh and a compactionpressure of 400 kg/cm². These findings demonstrate the potential of coffeeparchment as a viable source of solid fuel for heating applications.